Detailed crop suitability maps and an agricultural zonation scheme for Malawi: Spatial information for agricultural planning purposes - Benson, Todd; Mabiso, Athur; Nankhuni, Flora (Michigan State University, 2016)
This document describes a two-level agricultural zonation scheme to guide agricultural planning in Malawi. This scheme combines broad agricultural development domains – based upon a districtlevel analysis of agro-ecological potential; physical access to market; and population density – with an extensive set of detailed, more locally relevant crop suitability maps to determine where agricultural development investments might best be located within a relevant development domain.